2010
DOI: 10.3399/bjgp10x502100
|View full text |Cite
|
Sign up to set email alerts
|

How ready is general practice to improve quality in chronic kidney disease? A diagnostic analysis

Abstract: BackgroundChronic kidney disease (CKD) is associated with increased cardiovascular mortality and morbidity as well as progression to established renal failure. Interventions in primary care, particularly the lowering of blood pressure in individuals with CKD and proteinuria and diabetes, can slow disease progression. This evidence base is codified in national guidance and in a simplified form in pay-forperformance targets. Prior to conducting the QICKD study -a cluster of quality-improvement interventions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 19 publications
9
83
1
Order By: Relevance
“…Analysis also highlighted how anxiety surrounding disclosure influenced, and was shaped by, the organisation of care for people with CKD and associated long-term conditions. initial themes raised by Crinson et al 8 and sought to identify processes underpinning the implementation of CKD management in primary care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis also highlighted how anxiety surrounding disclosure influenced, and was shaped by, the organisation of care for people with CKD and associated long-term conditions. initial themes raised by Crinson et al 8 and sought to identify processes underpinning the implementation of CKD management in primary care.…”
Section: Resultsmentioning
confidence: 99%
“…8 NPT provided a framework to explore in greater detail the interactional work that occurs in clinical encounters and within an organisation. 12,13 Practices participating in a CLAHRC CKD Collaborative were purposively sampled, 14 as this approach provided an opportunity to explore attempts to implement CKD management in primary care.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Underlying factors are that the GP's confidence in treating CKD is lower than in treating diabetes and hypertension, and that blood pressure targets in CKD are often regarded with scepticism. 27,28 A discussion is ongoing with regard to optimal blood pressure targets. 29 Systolic blood pressure of <120 mmHg is associated with stroke and diastolic blood pressure of <60 mmHg is associated with increased mortality in older people who are frail.…”
Section: Discussionmentioning
confidence: 99%
“…7 Utilising Editorials particular groups from the Cochrane Collaboration, they scoured the literature for evidence of changes in practice that lead to a clearly defined endpoint: the reduction of systolic blood pressure. They found only nine studies with significant rigour that demonstrated that changes in practice, nurse, or pharmacist can improve blood pressure control, which leads to better outcomes for these patients.…”
mentioning
confidence: 99%